Elucidating mechanisms of ferroptosis regulation: the roles of peroxiredoxin 6 and cellular lipid composition - Inague, Alex (2023)
Ferroptosis is a form of non-apoptotic cell death that depends on iron-mediated phospholipid peroxidation. With its name coined 11 years ago, ferroptosis is now a rapidly growing research topic, including its potential application in combating tumors resistant to conventional therapies. Therefore, elucidating the mechanisms of ferroptosis regulation is essential to uncover potential molecular targets that can make cells more or less resistant to this type of cell death. Various ferroptotic regulators have already been characterized, such as the enzymes ACSL4 and GPX4. In this thesis, we explored three additional factors that regulate and/or impact ferroptotic cell death: the protein PRDX6, the metabolite 7-DHC, and cellular lipid composition. Using the A-375 cell line, we found that the knockout of PRDX6 leads to increased sensitivity to ferroptosis. According to available literature, the membrane repair and anti-ferroptotic function of PRDX6 are linked to two main enzymatic functions: phospholipase A2 (PLA2) and peroxidase activities. We were unable to identify PLA2 activity through the use of liposomes or micelles and high-performance liquid chromatography analysis. Additionally, while our data demonstrate that PRDX6 exhibits peroxidase activity against H2O2, the relevance of this enzyme in controlling lipid hydroperoxide levels is still unclear. In mouse embryonic fibroblasts, overexpression of PRDX6 cannot sustain cell growth in the absence of GPX4, indicating that PRDX6 may have insufficient peroxidase action. On the other hand, we found that PRDX6 knockout promotes a decrease in the expression of selenoproteins, including GPX4 itself, one of the main regulators of ferroptosis. Our data indicate that the function of PRDX6 is linked to the selenocysteine biosynthesis machinery, likely in a parallel pathway to selenocysteine lyase (SCLY) enzyme. Experiments with recombinant PRDX6 further suggest that this protein can bind to different selenium compounds, suggesting a possible role in intracellular selenium transport. Another crucial factor influencing cell sensitivity to ferroptosis is its lipid composition, for instance the content of sterols. Through the use of liposomes, we identified an antioxidant role for 7-DHC, which inhibits the peroxidation of phospholipids when they are subjected to iron-catalyzed radical oxidation. 7-DHC, like other lipophilic antioxidants, enhances membrane resistance against permeability generated under oxidative stress conditions. Using various strains of S.cerevisiae, we also demonstrated that this antioxidant effect is not exclusive to 7-DHC but is common to other sterols that also possess conjugated double bonds in the B-ring, such as ergosterol. Finally, through a comprehensive and detailed lipid analysis (lipidomics), we found that the global cellular lipid composition (lipidome) can provide a good indicator of the sensitivity of breast epithelial cell lines to ferroptosis during photodynamic therapy application. The lipid remodeling of these cell lines was mapped, revealing significant lipid changes resulting from the treatment.